Digital education training for teachers—Learnings from Austria - Hörmann, Corinna; Kuka, Lisa; Schmidthaler, Eva; Sabitzer, Barbara (Frontiers in Education, 2024)
The rapid evolution of digital technology has necessitated a shift in educational paradigms, particularly in teacher training and continuous professional development. This paper presents a study that explores Austrian teachers' attitudes toward digital education training and their preferences for in-service training modalities. Data were collected from a comprehensive survey involving about 600 Austrian secondary public school teachers and analyzed using quantitative and qualitative methods to reveal preferences and constraints in digital education in-service training, including the preferred modalities, the support required, and the teachers' motivations for engaging with training. Key findings from the study indicate that Austrian teachers generally have a positive perception of their autonomy in teaching digital education. Additionally, the study reveals that teachers are willing to participate in in-service training under specific conditions. This willingness is influenced by factors such as the flexibility of the training schedule, the provision of support resources, and the balance between professional obligations and personal time. The study highlights a broader trend toward flexibility and efficiency in in-service teacher training, acknowledging teachers' time constraints and the importance of maintaining a work-life balance. The findings suggest that flexible and supportive training environments can enhance teachers' engagement with digital education, ultimately benefiting their teaching practices and student outcomes. Overall, this study underscores the importance of adapting in-service teacher training to meet the needs of teachers, promoting a more effective integration of digital education.